Successful treatment of metachronous contralateral intratubular germ cell neoplasia with partial orchiectomy and low‐dose radiation in a patient previously treated for testicular carcinoma. Issue 10 (9th June 2019) - Schneller, Netta; Grimes, Amanda; Muscal, Jodi; Quintanilla, Norma; Mittal, Angela; Paulino, Arnold; Foster, Jennifer
Abstract: Intratubular germ cell neoplasia (ITGCN) of the testis is a precursor to testicular germ cell tumor (TGCT), which can lead to the development of invasive cancer. In patients with a history of previously treated unilateral TGCT, treatment for ITGCN of the contralateral testis needs to be balanced with the risks of subsequent infertility. Here, we present a 17‐ year‐ old patient with ITGCN diagnosed after treatment of contralateral nonseminomatous TGCT who was successfully treated with a partial orchiectomy followed by low‐dose radiation with preservation of his testosterone production.